‘I’m Feeling Insecure’: Hearing Voices of Indonesian Airlines Passenger Handlers Speak Up about English Use Problems in Their Job - Anisa Putri Cahyani; Joko Nurkamto; Sumardi - (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2018)
This present study hears voices of in-service airlines passenger handlers about conversations between them and passengers that occur in their work desks almost every day and their language problem. They will share their experience about conversations with passengers related to their job tasks or procedures, which are routine, and other non-procedural conversation topics which may occur several times. Data are gathered through in-depth interview with three in-service staffs from separated distinguished airports in Indonesia that already passed their first year working. This study reveals that in handling checking-in passengers the staffs need to be able to use English in order to demonstrate both procedural and non-procedural conversations. Dealing with their job, however, the staffs still find several language problems during the communication with English-speaking passengers which make them feel insecure. In this way, this article will present real report from in-service staffs that can be a valuable source for ESP teachers or practitioners, course developers, and researchers.